Targeted Resequencing of Deafness Genes Reveals a Founder MYO15A Variant in Northeastern Brazil. (15th November 2016) - Manzoli, Gabrielle N.; Bademci, Guney; Acosta, Angelina X.; Félix, Têmis M.; Cengiz, F.Basak; Foster, Joseph; Da Silva, Danniel S. Dias; Menendez, Ibis; Sanchez‐Pena, Isalis; Tekin, Demet; Blanton, Susan H.; Abe‐Sandes, Kiyoko; et al.
Summary: Identifying the genetic etiology in a person with hearing loss (HL) is challenging due to the extreme genetic heterogeneity in HL and the population‐specific variability. In this study, after excluding GJB2 variants, targeted resequencing of 180 deafness‐related genes revealed the causative variants in 11 of 19 (58%) Brazilian probands with autosomal recessive HL. Identified pathogenic variants were in MYO15A (10 families) and CLDN14 (one family). Remarkably, the MYO15A p.(Val1400Met) variant was identified in eight families from the city of Monte Santo in the northeast region of Brazil. Haplotype analysis of this variant was consistent with a single founder. No other cases with this variant were detected among 105 simplex cases from other cities of northeastern Brazil, suggesting that this variant is confined to a geographical region. This study suggests that it is feasible to develop population‐specific screening for deafness variants once causative variants are identified in different geographical groups.